0624 Addressing the Psychosocial Aspects of Narcolepsy: A Mixed-Methods Study. (12th April 2019) - Ong, Jason C; Fox, Rina S; Brower, Rylee; Mazurek, Sophia; Moore, Cameron
Abstract: Introduction: Medications can be effective for managing narcolepsy symptoms but people with narcolepsy (PWN) continue to report psychosocial distress. The purpose of this mixed-methods study was to assess current practices for addressing the psychosocial needs of PWN and to identify potential strategies that could be used to develop a psychosocial intervention. Methods: Twenty-nine adults (93% female, mean age = 31 years) with an established diagnosis of narcolepsy (Type I = 58.6%) completed on-line questionnaires (PHQ-9, PROMIS) and participated in focus groups. We conducted 10 focus groups led by a psychologist using live videoconferencing which consisted of questions pertaining to quality of life for PWN, current practices for addressing psychosocial health of PWN, and suggestions for developing a psychosocial intervention for PWN. Thematic analysis was used to reduce the qualitative data to key themes. Results: Clinically significant elevations (t-score>60) were reported on the PROMIS scales for depression (t-score=64.8, SEM=2.7), anxiety (t-score=66.3, SEM=2.6), fatigue (t-score=68.3, SEM=2.5), and sleep impairment (t-score=66.9, SEM=2.5). Elevations in depressive symptoms were reported on the PHQ-9 (M=15.79, SD=3.85). Qualitative data from focus groups revealed several key themes: 1) narcolepsy is poorly understood by the public and health care providers; 2) impact of narcolepsy has deleterious effects on self-image/self-worth, family and social relationships, and occupational functioning; 3) current health care practices are unsatisfactory for addressing psychosocial needs (e.g., provider does not understand or have time to address); 4) strong preference for working with clinicians who have training in narcolepsy; and 5) on-line platforms were the preferred format for receiving a psychosocial intervention due to accessibility. Conclusion: This study is the first to report standardized PROMIS scores for PWN, which revealed clinically significant elevations in depression, anxiety, fatigue, and daytime impairment. Qualitative data revealed challenges that PWN face in addressing their psychosocial needs and highlighted the gaps in the current health care system. Collectively, the findings demonstrate the need for a psychosocial intervention that directly addresses these clinical gaps for PWN. Support (If Any): This project was funded by a grant from Wake Up Narcolepsy.